A new species of Pseudochydorus Fryer, 1968 (Cladocera: Anomopoda: Chydoridae) from South-East Asia - Sinev, Artem Y.; Garibian, Petr G.; Gu, Yangliang (Zootaxa, 2016)
A new species of genus Pseudochydorus Fryer, 1968 (Cladocera: Anomopoda: Chydoridae) is described from South-East Asia. P. bopingi sp. nov. differs from Palearctic P. globosus (Baird, 1843) by a smaller size, well-developed flattened flange along the posterior margin of the valves, shorter rostrum, smaller ocellus, and details of antenna and thoracic limb II morphology. P. bopingi sp. nov. is known from South China and South Vietnam, but probably has a wider distribution. Our results suggest that populations from outside of Palearctic may belong to separate species as well.